2015
DOI: 10.5897/ajar2014.9425
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the relative resistance of different poultry breeds to Salmonella Typhimurium

Abstract: Salmonella infections originating from poultry are one of the major causes of food-borne diseases. To control Salmonella in poultry multifactorial approach is likely to be effective, and genetic resistance of poultry breeds to Salmonella infections may have valuable contribution. Experimental research was conducted to evaluate relative resistance of poultry breeds: Local, Fayoumi and Koekoek to Salmonella Typhimurium from November 2012 to May 2013. Total of 48 chicks were taken and half from each was randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…In our pilot study, we found the bacterial load in the resistant chicken breed ( K. favorella ) was lower than the bacterial load in the susceptible chicken breed (broiler). Our studies were in accordance with the previous studies, which showed the bacterial load in the local chicken was lower than other chicken breeds [ 39 , 40 ]. K. favorella showed minor lesions in the liver and spleen while the broiler chicken showed major necrotic lesions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our pilot study, we found the bacterial load in the resistant chicken breed ( K. favorella ) was lower than the bacterial load in the susceptible chicken breed (broiler). Our studies were in accordance with the previous studies, which showed the bacterial load in the local chicken was lower than other chicken breeds [ 39 , 40 ]. K. favorella showed minor lesions in the liver and spleen while the broiler chicken showed major necrotic lesions.…”
Section: Discussionsupporting
confidence: 93%
“…Resistance to salmonellosis in chicken greatly varies among the chicken line [ 52 ]. Due to breed differences, there is significant genetic heterogeneity in chicken for resistance to S. typhimurium [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella was detected two weeks postinfection, suggesting that the immunity of young chicks can provide early protection. However, over time, at four weeks, a decline was observed, indicating that resistance to Salmonella infection by older chickens may be associated with the activation of cellular and humoral immunity [ 43 ]. This scenario may provide information on the immune status of the poultry flock evaluated in our study.…”
Section: Discussionmentioning
confidence: 99%